Розробка спектрофотометричних методик кількісного визначення лікарських речовин, що містять вторинну аліфатичну аміногрупу - Жук, Юлія Миколаївна; Zhuk, Y. M. (Запорізький державний медичний університет, 2016)
Дисертація присвячена розробці високочутливих, простих у виконанні, валідованих та економічних спектрофотометричних методик кількісного визначення лікарських речовин, що містять вторинну аліфатичну аміногрупу на основі їх реакцій з сульфофталеїновими барвниками. Вивчено оптимальні умови перебігу реакцій досліджуваних лікарських барвниками та розраховано аналітичні показники чутливості. Встановлено стехіометричні коефіцієнти між реагуючими компонентами «лікарська речовина – реагент». Виділено та ідентифіковано продукти реакцій атенололу, бетаксололу гідрохлориду, бісопрололу фумарату, карведілолу та соталолу гідрохлориду з сульфофталеїновими барвниками, запропоновано хімізм перебігу реакцій. Розроблено прості, чутливі, експресні методики кількісного визначення 9 лікарських речовин, у складі 30 сучасних лікарських форм. Розроблені методики валідовані згідно вимог ДФУ і є прийнятними для виконання поставлених завдань. Based on the literature data the practicability of development of new spectrophotometric methods for the analysis of drugs containing the secondary aliphatic amino group using sulphophthalein dies as reagent was proved There were studied optimal conditions of the photometric reactions of investigational medicinal substances containing the secondary aliphatic amino group and sulphophthalein dies (carvedilol, metoprolol tartrate and sotalol hydrochloride with bromocresol purple, atenolol and nebivolol hydrochloride with bromthymol blue, betaxolol hydrochloride, salbutamol sulphate and phenylephrine hydrochloride with bromocresol green, bisoprolol fumarate with thymol blue). Optimal solvents (chloroform in the bisoprolol case and acetone in other circumstances), reagents and its quantity were selected. The reactions proceeded rapidly at room temperature, so temperature and time mode didn’t need correction in all cases. Lows of identification limit (0,67 – 5,88 mcg/ml) and ups of molar absorption coefficient (2,16•103–4,54•104) testified the reactions high тsensitivity. Defined stoichiometric ratio «reagent – drug substance» by molar ratio and isomolar series method. Molar ratio method results were consistent with isomolar series method results. Stoichiometric coefficients between reagents and drug substances were 1:1 in each case (atenolol, bisoprolol fumarate, betaxolol hydrochloride, carvedilol, metoprolol tartrate, nebivolol hydrochloride, sotalol hydrochloride and sulphophthalein dies). Reaction products of atenolol, betaxolol, bisoprolol, carvedilol, sotalol with sulphophthalein dies were isolated and identified. Products of reactions were ion-associates. It was proved by IR spectrophotometry, 1H NMR and 13C NMR spectrometry. Spectrophotometric methods for the quantitative determination of 9 drugs containing the secondary aliphatic amino group consisting of 30 commercial agents were developed and validated. Estimated total uncertainty of the analysis in each case did not exceed the critical value and suggests that methods will give correct results in other laboratories. Following validation characteristics as specificity, precision, linearity, accuracy and robustness were determined according to requirements of Ukrainian Pharmacopoeia Methods characterized by sufficient specificity to identify studied substances in presence of excipients. The linear dependence fundamentals were calculated. It was confirmed that developed methods are linear in selected ranges of concentrations. All requirements according to linear dependence parameters are met. Precision was determined in investigational medicinal substances in three different concentrations in the calibration range in three replicates. In all cases confidence interval does not more than the maximum indeterminateness of analysis. Accuracy was set for drug dosage forms using standard addition, model mixtures methods and by comparing results of the quantitative determination obtained by the developed method with the results of the arbitration procedure. The results showed the high accuracy of the proposed methods. The validation of robustness was carried out at methods development. Factors affect the absorbency such as the amount of reagent, stability test solutions over the time and the presence of water in the solvent were studied. It was established that sample solutions are stable for at least 30 minutes, and addition ±10% of reagents solution from the optimal to the sample solution has no effect on the absorbance value. The maximum amount of water which does not adversely affect the absorption spectra is 4%. Proved that for such validation characteristics as specificity, linearity, accuracy, range, precision and robustness developed methods of quantitative determination of studied drugs are corresponded to The Ukrainian Pharmacopoeia specification. Developed methods can be used in the laboratory of technical control department of drugs manufacturers and inspections of drugs quality control. The developed methods were implemented in the practice of drugs quality control laboratory. The developed methods are using in scientific and pedagogical process of Ukrainian higher education.
Spectrophotometric method development for the quantitative determination of drugs containing the secondary aliphatic amino group
Keywords: кількісний аналіз; спектрофотометрія; лікарські речовини; вторинна аліфатична аміногрупа; сульфофталеїнові барвники; валідація; analysis; spectrophotometry; drugs; secondary aliphatic amino group; sulphophthalein dies; validation